Investigasi Tingkat Kecemasan Mahasiswa Sains dan Pendidikan Sains Terhadap Mata Kuliah Dasar - Yusna, Nabillah; Ramli, Munasprianto; Muslim, Buchori (Universitas Pahlawan Tuanku Tambusai, 2024)
Chemistry lessons in the world of education are one of the lessons that are considered difficult. Chemistry is not only found in the High School period but also found at the University level. The Department of Science apart from Chemistry also re-learns this subject with Basic Chemistry courses in the Biology and Physics majors. This creates anxiety for students who are less interested in Basic Chemistry courses. The purpose of this study was to determine the level of anxiety of students of science and science education in basic chemistry subjects at UIN Syarif Hidataullah Jakarta. The Mixed Method Research. Participants were selected using a convenience sampling approach, totaling 224 students. The instrument used was 36 statement items in the questionnaire and interviews. Questionnaire data were processed by descriptive statistics and interviews with thematic analysis. The results showed that the difference in anxiety levels between students and science education, namely the Faculty of Tarbiyah and Teacher Training (FITK) had higher anxiety, namely Aspect 1 FITK had a proportion of 41.18% and FST 40.09%, in Aspect 2 FITK had a proportion of 34 .69% and 34.39% FST and in Aspect 3: FITK has a proportion of 32.75% and FST 31.05%. From the results of this study, it was found that science education students had higher levels of anxiety than pure science students.